Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized for You

we will pick new questions that match your level based on your Timer History

Track Your Progress

every week, we’ll send you an estimated GMAT score based on your performance

Practice Pays

we will pick new questions that match your level based on your Timer History

Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here.

It appears that you are browsing the GMAT Club forum unregistered!

Signing up is free, quick, and confidential.
Join other 500,000 members and get the full benefits of GMAT Club

Registration gives you:

Tests

Take 11 tests and quizzes from GMAT Club and leading GMAT prep companies such as Manhattan GMAT,
Knewton, and others. All are free for GMAT Club members.

Applicant Stats

View detailed applicant stats such as GPA, GMAT score, work experience, location, application
status, and more

Books/Downloads

Download thousands of study notes,
question collections, GMAT Club’s
Grammar and Math books.
All are free!

Thank you for using the timer!
We noticed you are actually not timing your practice. Click the START button first next time you use the timer.
There are many benefits to timing your practice, including:

I know how to solve this by plugging in numbers and could arrive at the right answer. I want to learn how to solve this using algebra. When I tried with algebra I get answer as A. Can some please verify my steps and explain me what I am missing? Thank you.

1. -x = y +z ==> x+y=z (This is 1. and satisfies the question with different values of y and z for a negative x) x=y+z ==> is not the same as given equation. So A is sufficient.

I know how to solve this by plugging in numbers and could arrive at the right answer. I want to learn how to solve this using algebra. When I tried with algebra I get answer as A. Can some please verify my steps and explain me what I am missing? Thank you.

1. -x = y +z ==> x+y=z (This is 1. and satisfies the question with different values of y and z for a negative x) x=y+z ==> is not the same as given equation. So A is sufficient.

2. Clearly insufficient.

|x| = y + x

(A) x = y + z AND/IF x > 0 (B) x = - ( y + z ) AND/IF x <0

I don't get Statement (1)

Shouldn't it be x = - y - z ??

But this is insufficient because we have to have the condition that x > 0

Statement (2)

x < 0 <-- insufficient (this is the condition we are looking for in statement (1))

Clearly, Statement (1) and Statement (2) = (C) _________________

Far better is it to dare mighty things, to win glorious triumphs, even though checkered by failure... than to rank with those poor spirits who neither enjoy nor suffer much, because they live in a gray twilight that knows not victory nor defeat. - T. Roosevelt

I know how to solve this by plugging in numbers and could arrive at the right answer. I want to learn how to solve this using algebra. When I tried with algebra I get answer as A. Can some please verify my steps and explain me what I am missing? Thank you.

1. -x = y +z ==> x+y=z (This is 1. and satisfies the question with different values of y and z for a negative x) x=y+z ==> is not the same as given equation. So A is sufficient.

2. Clearly insufficient.

|x| = y + x

(A) x = y + z AND/IF x > 0 (B) x = - ( y + z ) AND/IF x <0

I don't get Statement (1)

Shouldn't it be x = - y - z ??

But this is insufficient because we have to have the condition that x > 0

Statement (2)

x < 0 <-- insufficient (this is the condition we are looking for in statement (1))

Clearly, Statement (1) and Statement (2) = (C)

Statement 1, x=-y-z is same as -x=y+z. and this implies x<0 and hence the statement should be sufficient. This is where I got lost.

I know how to solve this by plugging in numbers and could arrive at the right answer. I want to learn how to solve this using algebra. When I tried with algebra I get answer as A. Can some please verify my steps and explain me what I am missing? Thank you.

1. -x = y +z ==> x+y=z (This is 1. and satisfies the question with different values of y and z for a negative x) x=y+z ==> is not the same as given equation. So A is sufficient.

2. Clearly insufficient.

|x| = y + x

(A) x = y + z AND/IF x > 0 (B) x = - ( y + z ) AND/IF x <0

I don't get Statement (1)

Shouldn't it be x = - y - z ??

But this is insufficient because we have to have the condition that x > 0

Statement (2)

x < 0 <-- insufficient (this is the condition we are looking for in statement (1))

Clearly, Statement (1) and Statement (2) = (C)

Statement 1, x=-y-z is same as -x=y+z. and this implies x<0 and hence the statement should be sufficient. This is where I got lost.

Yeah I also got this wrong the first time because I thought Statement (1) was already sufficient. However, we need Statement (2). _________________

Far better is it to dare mighty things, to win glorious triumphs, even though checkered by failure... than to rank with those poor spirits who neither enjoy nor suffer much, because they live in a gray twilight that knows not victory nor defeat. - T. Roosevelt

I know how to solve this by plugging in numbers and could arrive at the right answer. I want to learn how to solve this using algebra. When I tried with algebra I get answer as A. Can some please verify my steps and explain me what I am missing? Thank you.

1. -x = y +z ==> x+y=z (This is 1. and satisfies the question with different values of y and z for a negative x) x=y+z ==> is not the same as given equation. So A is sufficient.

2. Clearly insufficient.

Did you copy this problem down correctly? -x=y+z =/=> x+y=z.

I know how to solve this by plugging in numbers and could arrive at the right answer. I want to learn how to solve this using algebra. When I tried with algebra I get answer as A. Can some please verify my steps and explain me what I am missing? Thank you.

1. -x = y +z ==> x+y=z (This is 1. and satisfies the question with different values of y and z for a negative x) x=y+z ==> is not the same as given equation. So A is sufficient.

2. Clearly insufficient.

|x| = y + x

(A) x = y + z AND/IF x > 0 (B) x = - ( y + z ) AND/IF x <0

I don't get Statement (1)

Shouldn't it be x = - y - z ??

But this is insufficient because we have to have the condition that x > 0

Statement (2)

x < 0 <-- insufficient (this is the condition we are looking for in statement (1))

Clearly, Statement (1) and Statement (2) = (C)

Statement 1, x=-y-z is same as -x=y+z. and this implies x<0 and hence the statement should be sufficient. This is where I got lost.

This is where you're incorrect. -x=y+z alone does not imply that x<0 without the condition that y+z >0.

Re: Is |x| = y + z? (1) x + y = z (2) x < 0 [#permalink]

Show Tags

09 Jun 2012, 14:13

Expert's post

2

This post was BOOKMARKED

pgmat wrote:

Is |x| = y + z?

(1) x + y = z (2) x < 0

I know how to solve this by plugging in numbers and could arrive at the right answer. I want to learn how to solve this using algebra. When I tried with algebra I get answer as A. Can some please verify my steps and explain me what I am missing? Thank you.

1. -x = y +z ==> x+y=z (This is 1. and satisfies the question with different values of y and z for a negative x) x=y+z ==> is not the same as given equation. So A is sufficient.

2. Clearly insufficient.

The answer to this question is E, not C.

Consider below 2 cases: \(x=-1\), \(y=1\) and \(z=0\) --> \(|x|=1\) and \(y+z=1\) --> answer YES; \(x=-1\), \(y=2\) and \(z=1\) --> \(|x|=1\) and \(y+z=3\) --> answer NO.

I think you refer to the following question:

Is \(|x|=y-z\)?

Note that \(y-z\) must be \(\geq{0}\), because absolute value (in our case \(|x|\)) can not be negative.

Generally question asks whether \(y-z\geq{0}\) and whether the difference between them equals to \(|x|\).

(1) x + y = z --> \(-x=y-z\) if \(x>0\) --> \(y-z\) is negative --> no good for us; if \(x\leq{0}\) --> \(y-z\) is positive --> good. Two possible answers not sufficient;

(2) \(x<0\) Not sufficient (we need to know value of y-z is equal or not to |x|)

Re: Is |x| = y + z? (1) x + y = z (2) x < 0 [#permalink]

Show Tags

17 Aug 2012, 23:08

Bunuel wrote:

pgmat wrote:

Is |x| = y + z?

(1) x + y = z (2) x < 0

I know how to solve this by plugging in numbers and could arrive at the right answer. I want to learn how to solve this using algebra. When I tried with algebra I get answer as A. Can some please verify my steps and explain me what I am missing? Thank you.

1. -x = y +z ==> x+y=z (This is 1. and satisfies the question with different values of y and z for a negative x) x=y+z ==> is not the same as given equation. So A is sufficient.

2. Clearly insufficient.

The answer to this question is E, not C.

Consider below 2 cases: \(x=-1\), \(y=1\) and \(z=0\) --> \(|x|=1\) and \(y+z=1\) --> answer YES; \(x=-1\), \(y=2\) and \(z=1\) --> \(|x|=1\) and \(y+z=3\) --> answer NO.

I think you refer to the following question:

Is \(|x|=y-z\)?

Note that \(y-z\) must be \(\geq{0}\), because absolute value (in our case \(|x|\)) can not be negative.

Generally question asks whether \(y-z\geq{0}\) and whether the difference between them equals to \(|x|\).

(1) x + y = z --> \(-x=y-z\) if \(x>0\) --> \(y-z\) is negative --> no good for us; if \(x\leq{0}\) --> \(y-z\) is positive --> good. Two possible answers not sufficient;

(2) \(x<0\) Not sufficient (we need to know value of y-z is equal or not to |x|)

(1)+(2) Sufficient.

Answer: C.

Hope it's clear.

Hi ,

Though it looks reasonable , I am not sure on what is wrong with this logic.

1. -x = y +z ==> x+y=z (This is 1. and satisfies the question with different values of y and z for a negative x) x=y+z ==> is not the same as given equation. So A is sufficient.

Re: Is |x| = y + z? (1) x + y = z (2) x < 0 [#permalink]

Show Tags

18 Aug 2012, 01:00

pgmat wrote:

Is |x| = y + z?

(1) x + y = z (2) x < 0

I know how to solve this by plugging in numbers and could arrive at the right answer. I want to learn how to solve this using algebra. When I tried with algebra I get answer as A. Can some please verify my steps and explain me what I am missing? Thank you.

1. -x = y +z ==> x+y=z (This is 1. and satisfies the question with different values of y and z for a negative x) x=y+z ==> is not the same as given equation. So A is sufficient.

2. Clearly insufficient.

given that x = y+z or -x=Y+z

so 1. x+Y = z..... not sufficient 2. it does not tell everything either... so not sufficient..

together.... -x+y = z

-x = -y+z, hence not same as given in the question, hence the answer to the main question is NO and with C option we are answering it. _________________

Regards, Harsha

Note: Give me kudos if my approach is right , else help me understand where i am missing.. I want to bell the GMAT Cat

Re: Is |x| = y + z? (1) x + y = z (2) x < 0 [#permalink]

Show Tags

20 Aug 2012, 13:33

pgmat wrote:

Is |x| = y + z?

(1) x + y = z (2) x < 0

I know how to solve this by plugging in numbers and could arrive at the right answer. I want to learn how to solve this using algebra. When I tried with algebra I get answer as A. Can some please verify my steps and explain me what I am missing? Thank you.

1. -x = y +z ==> x+y=z (This is 1. and satisfies the question with different values of y and z for a negative x) x=y+z ==> is not the same as given equation. So A is sufficient.

2. Clearly insufficient.

(1) \(x = y-z\). Then \(|x|=|y-z|\) which is either \(y-z\) or \(z-y.\) In order to have \(y+z=y-z\), necessarily \(z=0\) and also \(y\geq0.\) In order to have \(y+z=z-y\), necessarily \(y=0\) and also \(z\geq0.\) Obviously not sufficient.

(2) Clearly not sufficient.

(1) and (2) We are in the case \(x=y-z<0\) so \(|x|=z-y\). For \(|x|=y+z\) as seen above we need \(y=0\) and \(z\geq0.\) Neither condition is guaranteed. Not sufficient.

Answer E _________________

PhD in Applied Mathematics Love GMAT Quant questions and running.

Hi Bunuel! I have a doubt. |x|= y+z gives us two equations.. X= y+ z or -x= y+z Statement one says x+y=z .. It is not possible to get the above mentioned statements with this equation. Statement two says x<0 ..this should be sufficient to answer right?

Similarly. In the question |x|= y-z. We can x= y-z and -x= y-z Statement one by substituting we get -x= y-z so this should be suffice to right?

Hi Bunuel! I have a doubt. |x|= y+z gives us two equations.. X= y+ z or -x= y+z Statement one says x+y=z .. It is not possible to get the above mentioned statements with this equation. Statement two says x<0 ..this should be sufficient to answer right?

Similarly. In the question |x|= y-z. We can x= y-z and -x= y-z Statement one by substituting we get -x= y-z so this should be suffice to right?

In the question |x|= y-z. We get two equations I.e.(removing the modulus . x= y-z and -x= y-z Statement one says x+z =y Therefore by substituting we get -x= y-z. so this should be suffice to answer right? As the question stem also has the same equation.

In the question |x|= y-z. We get two equations I.e.(removing the modulus . x= y-z and -x= y-z Statement one says x+z =y Therefore by substituting we get -x= y-z. so this should be suffice to answer right? As the question stem also has the same equation.

Posted from my mobile device

Since the correct answer is E, then this is obviously not right.

If \(x\geq{0}\), the questions asks: is \(x=y+z\)? If \(x<{0}\), the questions asks: is \(-x=y+z\)?

When we combine the statements, since it's given that x<0, the questions becomes: is \(-x=y+z\). From (1) we have that \(-x=y-z\), which is not sufficient to get whether \(-x=y+z\).

Thanks to another GMAT Club member, I have just discovered this valuable topic, yet it had no discussion for over a year. I am now bumping it up - doing my job. I think you may find it valuable (esp those replies with Kudos).

Want to see all other topics I dig out? Follow me (click follow button on profile). You will receive a summary of all topics I bump in your profile area as well as via email. _________________

So, my final tally is in. I applied to three b schools in total this season: INSEAD – admitted MIT Sloan – admitted Wharton – waitlisted and dinged No...

HBS alum talks about effective altruism and founding and ultimately closing MBAs Across America at TED: Casey Gerald speaks at TED2016 – Dream, February 15-19, 2016, Vancouver Convention Center...